Порівняльний аналіз стану та тенденцій заощаджень домогосподарств України - Іванько, А. В.; Македон, Г. М.; Ivanko, А.; Makedon, Н. (ЦНТУ, 2017)
Представлено результати порівняльного аналізу стану та тенденцій заощаджень домогосподарств України й інших країн світу. Аналіз виконаний за показниками: норма валових заощаджень; частка домашніх господарств у валових заощадженнях в економіці; абсолютний приріст заощаджень, темп приросту заощаджень; обсяги і середня норма заощаджень; чисті заощадження в обсязі наявних доходів домогосподарств. Встановлено факт суттєвого погіршення ситуації із заощадженнями домогосподарств України останніми двома роками із рівнем 0,98 % від наявного доходу внаслідок низького рівня їх добробуту. The purpose of the article is analyzing of the state and identifying the trends in household savings of Ukraine compared with other countries. It was confirmed that savings reflects the level of welfare, since savings can afford only those households that satisfy their basic needs for food, providing accommodation, training, recreation and more. The results of the comparative analysis of state and trends in household saving of Ukraine and other countries have been presented. The analysis was made for indicators: gross savings rate; share of households in gross savings in the economy; absolute growth of savings; growth rate of savings; volumes and average rate of savings; net savings in the amount of available household income. The existence of opposite tendencies (and their corresponding conditional two periods) has been established in savings: with the growth of their volumes in the period of 2006-2010 and their decrease in the period of 2011-2015. In the conditionally of the first analyzed period, the level of savings in Ukraine was closer to the level of savings in France, and in the conventional second period - to the level of savings in Japan and Finland. The savings of households in Ukraine over the past two years were at 0.98% of the available income due to the low level of their well-being.
Comparative analysis of state and tendencies of households saving of Ukraine
Keywords: домогосподарства; стан заощаджень домогосподарств; тенденції зміни заощаджень домогосподарств; порівняльний аналіз; економічні пропорції розвитку країни; цикли суспільного відтворення; households; state of household savings; trends in household savings; comparative analysis; proportion of economic development; cycles of public reproduction